The Burden of Nocturia Among Middle-Aged and Older Women - Hsu, Amy (Obstet Gynecol, 2015)
OBJECTIVE: To examine the prevalence, predictors and effects of nocturia in women, and evaluate overlaps with established urinary tract disorders. METHODS: This was a cross-sectional analysis of 2,016 women, aged 40 years and older, recruited from Kaiser Permanente Northern California from 2008 to 2012. Nocturia and other urinary symptoms were assessed using structured interviewer-administered questionnaires. Nocturia was defined as patient-reported nocturnal voiding of two or more times per night over a typical week. RESULTS: Thirty-four percent (n=692) reported nocturia, and 40% of women with nocturia reported no other urinary tract symptom. Women with nocturia were older (mean age 58 versus 55) (OR per 5-year increase 1.21 [95% CI, 1.12-1.31]) more likely Black (45%) (OR 1.75, [95% CI, 1.30-2.35]) or Latina (37%) (OR 1.36 [95% CI, 1.02-1.83]) versus non-Latina White (30%), have worse depression (mean Hospital Anxiety and Depression Scale (HADS) score 3.8 versus 2.8)(OR per 1-point increase in HADS score 1.08 [95% CI, 1.04-1.12]) and worse mobility (mean Timed Up-and-Go (TUG) 11.3 versus 10 seconds) (OR per 5-second increase in TUG 1.29 [95% CI, 1.05-1.58]). Nocturia occurred more among women with hysterectomy (53% versus 33%) (OR 1.78 [95% CI, 1.08-2.94]), hot flashes (38% versus 32%) (OR 1.49 [95% CI, 1.19-1.87]), and vaginal estrogen use (42% versus 34%) (OR 1.50 [95% CI, 1.04-2.18]). CONCLUSION: Nocturia is common in women and not necessarily attributable to other urinary tract disorders. Factors not linked to bladder function may contribute to nocturia risk, underlining the need for multi-organ prevention and treatment strategies.